2008
DOI: 10.2174/157016208786501508
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Unprotected Anal Intercourse in HIV Positive Men Attending an HIV/AIDS Clinic in Sydney§

Abstract: We examined the impact of cognitive and biomedical variables on unprotected anal intercourse between HIV-1 infected men and casual sexual partners in a Sydney-based cohort. Participants answered questionnaires examining insertive and receptive intercourse with and without ejaculation. They completed a modified optimism-scepticism scale, a sexual beliefs scale and a clinical/demographics questionnaire. CD4 count, blood and semen VL were assessed. 43 of 109 reported anal intercourse with HIV+ partners, 33 with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…In a recent study of UAI between HIV-positive men in this cohort and their casual male partners (HIV negative or unknown serostatus), we found that cognitive factors (treatment optimism and sexual beliefs) and biomedical factors (recent blood plasma HIV-RNA load [BPVL] and current sexually transmissible infection [STI]) were associated with different types of UAI. 6 Cognitive variables were predominately associated with UAI in that study. The current analysis was undertaken to determine whether similar variables predicted different types of UAI with regular partners in the same cohort.…”
Section: Introductionmentioning
confidence: 51%
“…In a recent study of UAI between HIV-positive men in this cohort and their casual male partners (HIV negative or unknown serostatus), we found that cognitive factors (treatment optimism and sexual beliefs) and biomedical factors (recent blood plasma HIV-RNA load [BPVL] and current sexually transmissible infection [STI]) were associated with different types of UAI. 6 Cognitive variables were predominately associated with UAI in that study. The current analysis was undertaken to determine whether similar variables predicted different types of UAI with regular partners in the same cohort.…”
Section: Introductionmentioning
confidence: 51%
“…While a number of empirical papers have published data on rates of IAI and RAI separately [13–15], we found few that reported rates of versatility. Most of those we found were based on data from the 1980s and early 1990s and reported what were considered at the time to be high levels of versatility, including 31% among U.S. MSM [16], 40% among British gay men [17], and 61% and 43% in two studies among Dutch gay men [10].…”
Section: Introductionmentioning
confidence: 73%
“…Unfortunately, a significant proportion of RAI among MSM is unprotected (Begley et al 2008; Chen et al 2003) and contributes to the growing number of new infections among MSM (Beyrer et al 2010). More recent data have clearly identified at risk MSM in the Global South (Baral et al 2012; Beyrer et al 2012).…”
Section: The Biology Of Rectal Hiv-1 Transmissionmentioning
confidence: 99%